The effect of firm size and transfer pricing on tax aggressiveness with institutional ownership as a moderating variable - Lubis, Amina Faralina; Wenten, I Ketut (WIM Solusi Prima, 2024)
This study aims to empirically prove the influence of firm size and transfer pricing on tax aggressiveness with institutional ownership as a moderating variable. The independent variables used in this research are firm size and transfer pricing. The dependent variable used in this research is tax aggressiveness and the moderating variable uses institutional ownership. The population in this study are basic materials sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sample selection method used purposive sampling, based on this method 14 (fourteen) companies were obtained, the data that was successfully used as a research sample was 8 (eight) companies with observations for 5 (five) years. The data used in this research is secondary data in the form of annual financial reports. The results of this research indicate that Firm Size and Transfer Pricing simultaneously have a significant effect on Tax Aggressiveness. The results of research conducted partially state that Firm Size and Transfer Pricing influence Tax Aggressiveness. Apart from that, Institutional Ownership is unable to moderate the influence of firm size and transfer pricing on Tax Aggressiveness.